Sejarah Toponim Prabumulih sebagai Sumber Pembelajaran Sejarah - Marini Marini; Kabib Sholeh; Sukardi Sukardi (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2019)
Abstract Prabumulih's toponym history is a source of the past from the origin of the name of the place to identity for the people who live in Prabumulih, which is a cultural outcome between local communities through history. The problem of this research is to find out how the history of the toponym of Prabumulih city can be used as a source of historical learning?. This study aims to determine the historical toponym values ​​of Prabumulih which can be used as a source of historical learning. The research method used is a qualitative descriptive method. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used are reducing data, presenting data, and drawing conclusions. From the results of the study it can be concluded that Prabumulih's toponym history has an important role for the school and for the community because it is a cultural outcome of community leaders who contain educational values ​​and historical values. Then the values ​​contained in Prabumulih's toponym history as a source of historical learning are historical values, social and cultural values, political values ​​and educational values. Which can be applied to Indonesian history subjects in class X at Prabumulih's Madrasah Aliyah Negeri 1 school, namely local history. Keywords: Prabumulih Toponym, History Learning.